2021
DOI: 10.1177/11786337211037355
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus (MRSA): Prevalence, Antimicrobial Susceptibility Pattern, and Detection of mecA Gene among Cardiac Patients from a Tertiary Care Heart Center in Kathmandu, Nepal

Abstract: Background: Methicillin Resistant Staphylococcus aureus (MRSA) is a significant human pathogen associated with nosocomial infections. mecA in the S. aureus is a marker of MRSA. The main objective of this study was to detect mecA and vanA genes conferring resistance in S. aureus among cardiac patients attending Sahid Gangalal National Heart Centre (SGNHC), Kathmandu, Nepal between May and November 2019. Methods: A total of 524 clinical samples (blood, urine, sputum) were collected and processed. Bacterial isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 65 publications
4
9
0
Order By: Relevance
“…In this study, E. coli was the most predominant Gramnegative bacterial isolate whereas S. aureus was the predominant Gram-positive bacterial isolate. This finding was in line with other studies reported from different hospitals/ laboratory settings in Nepal (37)(38)(39)(40). Observation of higher number of Gram-negative bacterial isolates in clinical specimens in different studies conducted in Nepal indicates Gram-negative bacteria are emerging as important health-care associated problems (41,42).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, E. coli was the most predominant Gramnegative bacterial isolate whereas S. aureus was the predominant Gram-positive bacterial isolate. This finding was in line with other studies reported from different hospitals/ laboratory settings in Nepal (37)(38)(39)(40). Observation of higher number of Gram-negative bacterial isolates in clinical specimens in different studies conducted in Nepal indicates Gram-negative bacteria are emerging as important health-care associated problems (41,42).…”
Section: Discussionsupporting
confidence: 92%
“…Among 27 isolates of S. aureus , 55.6% isolates were screened as methicillin-resistant. Some studies reported similar prevalence of MRSA [ 28 , 46 , 47 , 48 , 49 ] whereas other studies reported high prevalence of MRSA [ 19 , 50 ]. The variation in the prevalence of MRSA could be due to the difference in locations and time periods of the studies, infection control measures, antibiotic prophylaxis and treatments used in each hospital and the epidemic nature of these microorganisms [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, various research in Nepal looked on the phenotypic prevalence of MRSA infections [ 12 , 13 , 14 , 15 ]. MRSA frequency has been found to range from 15 to 69% in different hospitals and laboratory settings in Nepal [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. This study explores antimicrobial susceptibility patterns of clinical isolates of S. aureus from a tertiary hospital, examines their biofilm-forming capacity along with the detection of mec A gene.…”
Section: Introductionmentioning
confidence: 99%
“…Gun in 2021 reported the highest resistance to macrolides like erythromycin (87.29 %) [33]. In Nepal in 2021, all MRSA were resistant to penicillin, followed by erythromycin (94.9%) and none of MRSA was resistant to vancomycin [34]. The high rate of MRSA isolation and resistance to penicillin, ampicillin, erythromycin, etc.…”
Section: Discussionmentioning
confidence: 99%